Forest vegetation on sacred sites of the Tangier Peninsula (NW Morocco) - discussed in a SW-Mediterranean context - Frosch, Birgit; Deil, Ulrich; Freiburg (Phytocoenologia, 2011)
Forest stands on sacred sites can document climax or preclimax vegetation. However, little is known about the potential climax character of sacred sites in Morocco. We studied the vegetation of Muslim sacred sites and graveyards in rural regions of the Tangier Peninsula in Northwest Morocco. Sacred sites were chosen according to a pre-stratified random sampling method, taking climatic and edaphic patterns into account. In tree stands of 68 sacred sites 140 phytosociological relevés were sampled and classified. In an attempt to evaluate their degree of preservation, the best preserved holy forests were compared with reference data of similar forest communities, recorded mainly on non-sacred sites in southern Spain and Portugal, and northern Morocco and Algeria. The forested vegetation of sacred sites shows a great variety. Abiotic factors, such as substrate and bioclimate, and human interventions (grazing, fire, a.o.) were found to be important differentiating factors. Besides well-conserved forests, a broad spectrum of degradation stages was documented. Most stands still shelter the original tree species combination, but vertical structure and floristic composition of the herb layer are strongly modified. Processes related to anthropo-zoogenic pressure, like therophytization, ruderalisation and overaging of the tree layer occur despite religious taboos. Near-natural holy forests belong to various subtypes of the Teucrio baetici-Quercetum suberis and the Rusco hypophylli-Quercetum cocciferae. In comparison to forests on non-sacred sites, these holy forests are very well preserved, as is indicated by the presence of strict forest species of the Quercetalia ilicis and the Querco-Oleion sylvestris, by transgressives of the Quercetalia pubescentis, and by a high constancy and abundance of ombro- and mesophilous taxa. Moreover, the comparison of phytosociological data from Morocco and Spain indicated an Ibero-Mauretanian distribution of several Quercus suber communities. In conclusion, sacred groves often seem to represent the potential natural vegetation. Exceptions are sacred groves with Wild Olive, which occur in an ecoregion where a thermomediterranean Quercus suber forest is considered to be the climax.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: climax; degradation; Evergreen mediterranean forest; holy forest; maghreb; marabout; quercetea ilicis; sacred grove

Distribution , Ecology and Population Structure of Euphorbia monchiquensis , an Endemism in Southern Portugal (Silva Lusitana, 2004)
Euphorbia monchiquensis is, within the widespread and euryoecious E. paniculata- complex, an acidophilous subspecies, endemic in Southern Portugal. To evaluate the vulnerability of this taxon vis-a-vis disturbance and landuse changes, we studied the actual distribution, the population size, the ecological requirements and the coenological value of this taxon in the Serra de Monchique, a mountainous region in the Algarve Hinterland. Data sampling was between April and July 2001. The quite constant branching system of this half shrubby spurge allows to determine the age of the indivuduals from the plant architecture and therefore to study the demographic structure in a non-destructive way. 1618 individuals, clustered in 46 populations, have been registered in the Serra. 88% were in flower. Euphorbia monchiquensis is rare relative to its overall distribution. It shows a bimodal altitudinal and coenological pattern. The majority of the populations are concentrated in the most humid mid altitudes and on the luv-ward northwestern side of the Serra. A few populations occur in the dry lowlands, linked to riverine shrublets. The plant depends on a good water supply but does not need shadowing. Within its limited bioclimatic niche, the spurge has a certain capacity of recolonisation and is not extremely sensitive to disturbance. Humid forests of the Euphorbio monchiquensis-Quercetum canariensis are just one of the preferred sociological situations. The coenological spectrum includes pure cork oak forests, Castanea sativa coppices, Eucalyptus-afforestations, mantle communities (Lonicero-Rubetum, Rubo- Nerietum), Origanion virentis fringes, abandoned meadows and roadside verges. It was in this kind of secondary habitats with intermittent disturbance, that most of the juvenile plants could be stated. Only very few plantlings were found. Most of the recorded populations are well balanced in their medium age classes, others are overaged. A correlation between habitat qualities, the reproductive effort and the regeneration efficiency could not be found. Four inflorescence- -morphotypes can be distinguished. The inflorescence architecture becomes more complex with increasing age. Euphorbia monchiquensis is not an extremely endangered, but a vulnerable species. It can be threatened by the process of Eucalyptus afforestation and by the spontaneous spread of Acacia dealbata. To give a reliable answer to the extinction risk, further aspects of its life cycle, seed bank characteristics, and reproductive behaviour have to be studied.

Distribution , Ecology and Population Structure of Euphorbia monchiquensis , an Endemism in Southern Portugal - Fox, Xenia; Deil, Ulrich (Silva Lusitana, 2004)
Euphorbia monchiquensis is, within the widespread and euryoecious E. paniculata- complex, an acidophilous subspecies, endemic in Southern Portugal. To evaluate the vulnerability of this taxon vis-a-vis disturbance and landuse changes, we studied the actual distribution, the population size, the ecological requirements and the coenological value of this taxon in the Serra de Monchique, a mountainous region in the Algarve Hinterland. Data sampling was between April and July 2001. The quite constant branching system of this half shrubby spurge allows to determine the age of the indivuduals from the plant architecture and therefore to study the demographic structure in a non-destructive way. 1618 individuals, clustered in 46 populations, have been registered in the Serra. 88% were in flower. Euphorbia monchiquensis is rare relative to its overall distribution. It shows a bimodal altitudinal and coenological pattern. The majority of the populations are concentrated in the most humid mid altitudes and on the luv-ward northwestern side of the Serra. A few populations occur in the dry lowlands, linked to riverine shrublets. The plant depends on a good water supply but does not need shadowing. Within its limited bioclimatic niche, the spurge has a certain capacity of recolonisation and is not extremely sensitive to disturbance. Humid forests of the Euphorbio monchiquensis-Quercetum canariensis are just one of the preferred sociological situations. The coenological spectrum includes pure cork oak forests, Castanea sativa coppices, Eucalyptus-afforestations, mantle communities (Lonicero-Rubetum, Rubo- Nerietum), Origanion virentis fringes, abandoned meadows and roadside verges. It was in this kind of secondary habitats with intermittent disturbance, that most of the juvenile plants could be stated. Only very few plantlings were found. Most of the recorded populations are well balanced in their medium age classes, others are overaged. A correlation between habitat qualities, the reproductive effort and the regeneration efficiency could not be found. Four inflorescence- -morphotypes can be distinguished. The inflorescence architecture becomes more complex with increasing age. Euphorbia monchiquensis is not an extremely endangered, but a vulnerable species. It can be threatened by the process of Eucalyptus afforestation and by the spontaneous spread of Acacia dealbata. To give a reliable answer to the extinction risk, further aspects of its life cycle, seed bank characteristics, and reproductive behaviour have to be studied.
Keywords: age-states; conservation biology; landuse; plant architecture; reproduction; serra de monchique